Rotavirus-associated seizures and reversible corpus callosum lesion - Laizane, Gunta; Smane, Liene; Nokalna, Ieva; Gardovska, Dace; Feemster, Kristen A. (Acta medica Lituanica, 2019)
Rotavirus is a non-enveloped double-stranded RNA virus that causes severe gastroenteritis in children, but complications are rarely reported. Some reports have shown that rotavirus can induce diverse complications of the central nervous system, such as seizures, encephalopathy with a reversible splenial lesion, encephalitis, cerebral white matter abnormalities, and cerebellitis. Here, we present a 2-year-old patient with seizures, who had an isolated splenial lesion in the corpus callosum on neuroimaging, and the rotavirus antigen detected in faeces.